Electrochromic lithium nickel oxide by pulsed laser deposition and sputtering - Michael D. Rubin; Shi-Jie Wen; Thomas J. Richardson; John B. Kerr; Klaus von Rottkay; Jonathan L. Slack (Solar Energy Materials and Solar Cells, 1998)
Thin films of lithium nickel oxide were deposited by sputtering and pulsed laser deposition (PLD) from targets of pressed LiNiO2 powder. The composition and structure of these films were analyzed using a variety of techniques, such as nuclear-reaction analysis, Rutherford backscattering spectrometry (RBS), X-ray diffraction, infrared spectroscopy, and atomic-force microscopy. Crystalline structure, surface morphology and chemical composition of LixNi1−xO thin films depend strongly on deposition oxygen pressure, temperature as well as substrate–target distance. The films produced at temperatures lower than 600°C spontaneously absorb CO2 and H2O at their surface once they are exposed to the air. The films deposited at 600°C proved to be stable in air over a long period. Even at room temperature the PLD films are denser and more stable than sputtered films. RBS determined the composition of the best films to be Li0.5Ni0.5O deposited by PLD at 60 mTorr O2 pressure. Electrochemical tests show that the films exhibit excellent reversibility in the range 1.0–3.4 V versus lithium. Electrochemical formatting which is used to develop electrochromism in other films is not needed for the stoichiometric films. The optical transmission range is almost 70% at 550 nm for 150 nm-thick films. Devices made from these films were analyzed using novel reference electrodes and by disassembling after cycling.
Keywords: Lithium nickel oxide; pulsed laser deposition; sputtering

Analysis of Durability in Lithium Nickel Oxide Electrochromic Materials and Devices - Shi-Jie Wen; John B. Kerr; Michael D. Rubin; Jonathan L. Slack; Klaus von Rottkay (2nd International Meeting on Electrochromism, 1996)
Thin films of lithium nickel oxide were deposited by sputtering and laser ablation from targets of pressed nickel oxide and lithium oxide powders. These films were assembled into electrochromic test devices with tungsten oxide as the opposite electrode and a polymer electrolyte. Analysis of the failure modes was carried out at several levels: The composition and structure of the films were examined before and after cycling using a variety of techniques, such as infrared spectroscopy, nuclear-reaction analysis, Rutherford backscattering spectrometry, x-ray diffraction and atomic force microscopy. Absorption of water vapor was found to be a major factor determining the cyclic stability of the films. A new technique is described for incorporating reference electrodes made from an electronically isolated corner into devices. This structure enabled identification of potential problems associated with a particular interface. Finally, some of the devices were disassembled and the components examined. For example, a small quantity of the polymer was extracted and studied by gas chromatography and mass spectroscopy. Small organic fragments were discovered which correspond to expected weak points in the polymer structures.

Optical Modeling of a Complete Electrochromic Device - Klaus von Rottkay; Michael D. Rubin; John B. Kerr (2nd International Conference on Electrochromics, 1996)
Optical indices have been determined for thin films of all materials needed to model a typical electrochromic device. Two electrochromic materials, tungsten oxide and lithium nickel oxide, are widely used in electrochromic devices. The optical indices of the underlying transparent conductors as well as a polymer electrolyte were also analyzed. The optical data was obtained using a combination of variable-angle spectroscopic ellipsometry and spectroradiometry. The data was then fit to appropriate models of structure and dispersion in order to extract the optical indices of the materials. First, the optical indices of the transparent conductive substrates were obtained and fixed in the model. The best models correspond well to independent physical measurements of film structure, such as atomic-force microscopy and surface profiling. Surface roughness, gradient composition and other types of inhomogeneity are common in both the transparent conductors and electrochromic, resulting in particularly complex models. The polymer has a homogeneous structure, but obtaining optically smooth surfaces was a problem. Complete sets of data were produced over the entire solar spectrum for a range of colored states of the films. Using the data for each layer, a realistic electrochromic device was simulated.